Topical Polyethylene Glycol-Phage Ointment as a Therapy to Treat Burn-Wound Infection Using Mice Model - Mansoor, Karrar Jabbar; Kaabi, Sadeq Abdulridha Gatea (Al-Mustansiriyah Journal of Science, 2024)
Background: One of the most significant problems facing public health today is antimicrobial resistance. Pseudomonas aeruginosa is considered one of the most prevalent causes of healthcare-associated illnesses. Objective: The use of phages as a potential alternative therapeutic method for treating bacterial infections has been the subject of significant research to solve this predicament. Methods: The P. aeruginosa isolates that caused infections of burn wounds were collected from three hospitals in Baghdad. The VITEK system diagnosed and examined the isolates for their antibiotic sensitivity. As well as the phages were isolated and purified from sewage water samples from different sewer stations. After these steps, phages were examined by transmission electron microscopy to ensure the order and the families of these phages, and the tests of lytic activities of phages on the P. aeruginosa isolates were done to determine the best lytic ability of them to use for treatment wounds infections. Results: Burn-wound infections swabs culture showed a positive culture for 109 isolates as the following P. aeruginosa in 76(69.72%), Staphylococcus aureus16(14.67%), Acinetobacter baumannii 9(8.25%), Klebsiella pneumoniae 5(4.58%), Escherichia .coli 3(2.75%) obtained from burn wound infections, had a significant level of resistance to several antibiotics. Four bacteriophages were isolated: KM1, KM2, KM3, KM4 and KM5. KM5 is a mixture of phages referred to as a cocktail. The four phages and their cocktail exhibited significant lytic activity against P. aeruginosa. A total of four monophages and a cocktail were utilized in the preparation of the PEG-phage ointment. Conclusions: All monophages and their cocktail could completely clear bacterial infection in 17 days. KM3 and KM4 PEG-phage ointments demonstrated more potent healing activity than standard, which required 12 days for full recovery, while the cocktail took 15 days (KM5). However, KM1 and KM2 took the same time as the standard, which is 17 days for burn wound infection treated with PEG-phage ointments, while the control, which did not receive any treatment, took 23 days to recover. KM1 and KM2 show less activity for healing burn wound infections from all five phage ointments.